Migration Drivers, the EU External Migration Policy and Crisis Management - Fulvio Attinà (Romanian Journal of European Affairs)
The present paper is a study of the response of the EU institutions and leaders to the inflow of irregular migrants from 2011 to 2016. The first section is the synthetic presentation of the migration drivers of our times at the global and local level. In section two, the citizens’ perception of the migrants as a threat is briefly discussed, and the border control and immigration policies of the EU are reviewed. In section three, the ‘Trans boundary crisis management’ model opted for analysing the EU migration crisis management is presented. Section four presents the analysis of the four scenarios of the European management of the current migration crisis. In the concluding section, the results of the analysis are summarily discussed. The analysis demonstrates that the EU leaders have been late in detecting the characteristics of the phenomenon and have not conceded to reconcile their conventional view to the features of the current migration. They have been unable to make response decisions well timed and acceptable to all. Lastly, they have been unable to stand firm on those management decisions they agreed on with difficulty and failed to formulate a shared message about the crisis and communicate credible messages to citizens about their ability to manage it.